A study if effectiveness of utilizing Instagram to create self-branding among the youth in Klang Valley - Wong, Chun Lam (2024)
Instagram has evolved into a platform that allows people to share their daily lives on it, but it also allows people to use it as a working tool, as it can aid in the creation of self-branding. This research aims to investigate the effectiveness of utilizing Instagram to create self-branding of oneself among the youth in the Klang Valley, Malaysia by using Self-Presentation Theory. The Quantitative Method will be utilised in the questionnaires which are distributed to 50 respondents who stayed in Klang Valley Malaysia with the aged between 18 to 24 years old who are active on Instagram. The purpose of this study is to determine how effective it is to use Instagram for self-branding in comparison to other platforms. All data were gathered using a Google Form and Microsoft Excel to have a better understanding on the effectiveness of creating self-branding on Instagram.